Rozwój koncepcji integracji europejskiej w szkole historycznej - Cymerman, Anna (The Development of the European Integration Idea in the Light of the Historical School, 2007)
A big amount and variety of integrate concepts presented during the 19th century and the first half of the 20th century in Europe didn't contribute to creation of such a concept that would take into account requirements of individual states. It is possible to detect bases of inefficacy of these ideas in nationalistic stream, which excludes phenomenon of international integration from definition. Particularly strong nationalistic motives and aspirations were visible in German integrate concepts. This fact did not promote realization of idea of unifying European continent. Superiority of interest of individual state has predetermined inefficacy of process of integration before World War II. Post-war integrate ideas could be based in small degree on earliest experiences in this range. Destroyed during the war, European states craved for stability. The process of unifying was supposed to help reconstructing European economy. The integration process has been based on equal treatment of all members of the EU. Personal interest of state member cannot be contradictory to interests of the European Union as a whole. On the one hand the 19th century's ideas regarding European integration represent an intellectually interesting part of integrate idea that also has weak sides. On the other hand, they have allowed the development of research in this range and in range of economic history, economic geography, and economic theory of localization. Therefore, they represent an inspiring element of human intellectual investigation.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonomia i Międzynarodowe Stosunki Gospodarcze (14); 2007; nr 1164, s. 232-244